(untitled) (Biodiversitas Journal of Biological Diversity, 2010)
Reyahi-Khoram M, Norisharikabad V (2011) Biodiversities and limiting factors of Lashgardar Protected Area (LPA), Hamadan Province, Iran. Biodiversitas 12: 216-221. Lashgardar Protected Area (LPA) located in Hamadan Province in Iran, it is a mountainous and plain area and proximal to Malayer Township. In 1991, the region was known as a protected area for increasing wild animals’ population. This research has been conducted during 2001 through 2009. Plant and animal species of the region were identified and statistics of the population of animal flagship species were gathered. In this research, valid academic resources were used for identification of animal and plant species. Geographic Information System (GIS) has been used to evaluate the land as main tool. The software used was Arc View (version 3.2a) scale was 1/50,000. Due to cold mountainous climate, the region is covered by a wide diversity of trees, shrubs, grasses and herbs. There were 18 species of mammals as well as 75 bird species in LPA. Most abundant mammalian population belongs to wild sheep (558 animals) and the second abundance was related to wild goat (515 animals). Also, the most abundant bird species belong to ortolans. Result of the present study showed that construction of connection roads in vicinity the region, establishment of factories inside and around the region, military garrison, unauthorized grazing, unlawful hunting, and Ahangaran mine and rail road have all exposed put LPA to serious threat and danger. Key words: biodiversity, environment, Lashgardar, protected area, wildlife